Comparison between common traffic lights and three types of traffic lights with visual cycle a safety and capacity analysis - Spigolon, Luciana Gasparelo; Bezerra, Barbara Stolte [UNESP]; Bastos, Jorge Tiago; Ferraz, Antonio Clovis Pinto; Battistelle, Rosane Aparecida Gomes [UNESP] (FapUNIFESP (SciELO), 2015)
The objective of this paper is compare the common traffic lights (CTL) to three different types of traffic lights with countdown displays (SCD) and assess their effects on road safety and capacity. This comparison is required because the results found in the literature are divergent among countries and cities, and one of the SCD analyzed in our study is different from the SCD used worldwide. An observational before-after study was conducted to evaluate the safety and capacity in a period of one year before and one year after the implementation of the SCD in three Brazilian cities. The results indicate that the SCD models 1 and 3 had around 35%±14% reduction in the total number of accidents; the model 2, does not have significant reduction. In order to perform the capacity analysis a framework for data collection and an adaptation for estimation of initial lost time in each phase were developed. Considering the capacity analysis there was a reduction around 11% in the lost time in SCD model 1, 7% in SCD model 2 and 3% in SCD model 3. However the implications of this on capacity are trifle due to a small increase in the average headways for all SCD models compare to CTL.
Keywords: Before-after study; Traffic lights; Countdown time devices; Traffic safety